Seleção genotípica visando à precocidade em soja - Ribeiro, Flaviane de Oliveira (2018)
Obtaining early-maturity soybean cultivars that associate good agronomic performance has been the main focus of breeding programs. To assure the success of these programs, to obtain estimates of genetic and phenotypic parameters is of fundamental importance, since it aids the breeders to select the superior genotypes efficiently. Therefore, the objectives of this study were to estimate genetic and phenotypic parameters associated to Cycle 0 progenies of the early-maturity soybean recurrent selection program; to select good agronomic performance soybean progenies to southern region of Minas Gerais/Campo das vertentes. S0:1 progenies were evaluated in Lavras city during the crop year of 2015/2016. For each plot, one row of 2,0 m with two replications were adopted, in a 12 x 12 Lattice design (131 progenies + 12 parental). The S 0:2 progenies were evaluated during the summer of 2016/2017 crop year in Lavras, Nazareno and Itutinga cities. For these evaluations an 8 x 8 Lattice design (51 progenies + 13 parental), using one row of 3 m plots with three replications, were adopted. S0:3 progenies were evaluated during 2017/2018 crop year in Lavras, Itutinga and Ijaci cities. For the evaluation of these progenies, a 5 x5 lattice (12 progenies + 13 parental) were adopted. Each plot consists of two rows of 3 m with three replications. Days to flowering, absolute maturity, height of first pod insertion, plant height, lodging, and grain yield characters were evaluated. Data analysis were performed using Mixed Model methods. The genetic and phenotypic parameters, expected selection gain, realized heritability, correlated response were estimated, as well as the adjusted means frequency distribution. The estimates of components of variance evidence the presence of variability among the progenies, possibility the selection of superior genotypes. All evaluated progenies had good agronomic performance, allying early-maturity and good yield performance. When selecting earlymaturity progenies, it was observed reductions on days to flowering, plant height and height of first pod insertion, lodging and grain yield characters. Effect of genotypes x environments interaction for all evaluated characters were also observed.